Tinjauan Implementasi Nilai-Nilai Pancasila dalam Kehidupan Bermasyarakat - Indira Syifa Karai Handak; Dinie Anggraeni Dewi (Mahesa Research Center, 2021)
We must realize that the implementation of Pancasila in social life needs to be reviewed in depth, so that the cultivation of noble values and appreciation of Pancasila are not misinterpreted. This research study used a qualitative method or a descriptive approach. The rationale and the results of the discussion were obtained from the results of literature studies of various sources such as journals, articles and books. Then, the research obtained the results of the review that the implementation of Pancasila in society has not been carried out by all members of society, which could have a serious impact therein. One of the solutions in implementing Pancasila values as an Indonesian citizen, especially in society, is to have a sincere love for the country and an attitude of openness among fellow citizens. By understanding the review of the implementation of Pancasila, it is hoped that it will be able to enhance the actualization and existence of Pancasila by implementing it in daily life, in order to form a balanced country.